2011
DOI: 10.1039/c1cp20434c
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of ozone in oxygen-rich solar system ices via ionizing radiation

Abstract: The irradiation of pure molecular oxygen (O(2)) and carbon dioxide (CO(2)) ices with 5 keV H(+) and He(+) ions was investigated experimentally to simulate the chemical processing of oxygen rich planetary and interstellar surfaces by exposure to galactic cosmic ray (GCR), solar wind, and magnetospheric particles. Deposited at 12 K under ultra-high vacuum conditions (UHV), the irradiated condensates were monitored on-line and in situ in the solid-state by Fourier transform infrared spectroscopy (FTIR), revealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Recently, ozone formation has been studied in the laboratory using supra thermal oxygen atoms generated by energetic electrons or ions. [16][17][18] Jing et al 19 also performed experiments on the formation of ozone on bare silicates, but our present work and analysis do not lead to the same conclusions. We attribute the detection of high temperature signals at mass 32 a.m.u.…”
Section: Introductionmentioning
confidence: 56%
“…Recently, ozone formation has been studied in the laboratory using supra thermal oxygen atoms generated by energetic electrons or ions. [16][17][18] Jing et al 19 also performed experiments on the formation of ozone on bare silicates, but our present work and analysis do not lead to the same conclusions. We attribute the detection of high temperature signals at mass 32 a.m.u.…”
Section: Introductionmentioning
confidence: 56%
“…Molecular oxygen is accompanied by ozone in the presence of a UV or energetic radiation environment. For instance, it has been shown that solid O 3 is produced when frozen O 2 is irradiated with energetic ions (Baragiola et al 1999;Famá et al 2002;Ennis et al 2011), electrons (Lacombe et al 1997;Sivaraman et al 2007), and UV photons (Gerakines et al 1996;. These studies are important to ascertain the possibility of observing photosensitive icy "tracers" like O 3 on interstellar grains and planetary surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Within the mid-infrared band, the most pronounced band of ozone is located at 1055 cm −1 , and is associated with the ν 3 asymmetric stretching vibration33. Furthermore, a Fermi resonance band at 2100 cm −1 , associated with the ν 1 + ν 3 combination band, is evident, yet though with at least 4-times less intensity.…”
Section: Discussionmentioning
confidence: 95%